Profile of Gonad Development and Spawn Milkfish Broodstock, Chanos chanos Forskall G-1 with Hormonal Implantation Reared in The Controlled Tank - Dharma, Tony Setia; Zafran, Zafran (Indonesian Aquaculture Society (MAI), 2017)
This research was conducted in Institute for Mariculture Research and Development (IMRAD) using on concrete tanks 150 m³. The objective of this research was to know the performance and gonad maturations development and spawn activities of first generation (G-1) broodstock from individual selection. The experiment test of milkfish broodstock with weight size of 3,891.67±344.99 g were reared on tank. Fish were reared at initial density of 60 individuals fish in 150 m³ concrete tanks. The treatments were: with hormone (A) and without hormone (B) implantation. The doze of LHRH-a implant hormone was 50 µg/kg. The broodstock were reared using of standard procedure operational (SOP) for spawning and gonad maturations. The result of the experiment showed that fish with hormone implantation gave the better results in gonad development on stage of reproduction than fish without hormon implantation. The gonad maturations and development on male and female broodstock diameter of oocyte and sperm were 450 µm and positive 2 and 3, respectively. The broodstock was spawn on the continue rear culture in the tank. The frequency of spawning were 8 times (with hormone) and 4 times (without hormone implantation) with total number of egg was 1,660,000 and 500,000 pc, respectively. The quality of eggs were 55-95% for fertilities and index activity survival (SAI) after hatching larvae was 4-5 days.